Plasmodium falciparum biosynthesizes sulfoglycosphingolipids - Landoni, Malena (2007)
Sulfated glycosphingolipids are present on the surface of a variety of cells. They are active participants in adhesion processes in many systems and appear to be involved in the regulation of cell proliferation, differentiation and other developmental cellular events. However, the body of knowledge about synthesis, structure, and function of glycolipids in parasitic protozoa is very limited so far. In this work, we show by metabolic incorporation of [14C]palmitic acid, [14C]glucose and Na235SO4 that sulfoglycosphingolipids are biosynthesized in the three intraerythrocytic stages of Plasmodium falciparum. After saponification, purification of the labelled acidic components was achieved and two components named SPf1 and SPf2 were characterized. Chemical degradations and TLC analysis pointed out to sulfolipidic structures. Analysis by UV-MALDI-TOF mass spectrometry in the negative ion mode using nor-harmane as matrix showed for SPf2 a structure consisting in a disulfated hexose linked to a 20:1 sphingosine acylated with C18:0 fatty acid. Interestingly, parasite treatment with low concentrations of d,l-threo-phenyl-2-palmitoylamino-3-morpholino-1-propanol (PPMP) caused an arrest on parasite development associated to the inhibition of sulfoglycolipid biosynthesis. Taking into account that sulfoglycolipidic structures are currently involved in adhesion processes, our findings open the possibility to study the participation of this type of structures in the described aggregation phenomena in severe malaria and may contribute to clarify the pathogenesis of the disease. This report shows for the first time the synthesis of sulfoglycolipids in Apicomplexa.